The Careless Society—Dependency and Care Work in Capitalist Societies - Müller, Beatrice (Frontiers in Sociology, 2019)
The article analyzes the status of care work in capitalist societies. Care is characterized as a requirement in the context of human dependency and vulnerability, and care work is here deemed to be materialized and “thickly embodied” (Lanoix 2013) rather then as being affective labor (Hardt/Negri 2000). This conceptualization of care work is based on an care-ethical understanding and also on feminist leib-phenomenological theory that draws on the distinction between the physical body and the living body (German: Körper and Leib). Relational embodied care is devalued in capitalist societies which are thus built not only on unequal class relations at a very basic level but also on the cultural and economic devaluation and the externalization of elements of care to the private sphere where that care is mostly provided as unpaid and invisible work. The concept of value abjection (German: Wert-Abjektion) aims to illustrate and analyze these structural tendencies and it’s consequences experienced by care workers and the elderly as care receivers.